Monohydrocyanation of Symmetrical Azines Using Potassium Hexacyanoferrate(II) as an Environmentally Friendly Cyanide Source - Hu, Xiaochun; Li, Hongbo; Yang, Jingya; Li, Zheng (Synlett, 2014)
The monohydrocyanation of symmetrical azines to synthesize α-hydrazinonitriles using potassium hexacyanoferrate(II) as cyanide source and benzoyl chloride as a promoter under catalyst-free conditions is described. The advantages of this protocol are the environmentally friendly cyanide source, high yield, and simple work-up procedure.
Keywords: green chemistry; hydrocyanation; nucleophilic addition; synthetic methods; azines